2012
DOI: 10.21861/hgg.2011.73.02.13
|View full text |Cite
|
Sign up to set email alerts
|

Development Problems of the Žumberak Border Region

Abstract: Cilj rada bio je istražiti razvojne probleme Žumberka u kontekstu njegove periferič-nosti unutar Središnje Hrvatske te položaja uz državnu granicu sa Slovenijom. U skladu s tim razmotreni su problemi demografskog razvoja i demografskih struktura, socijalnoekonomskog razvoja, gravitacijske usmjerenosti te opremljenosti i upotrebe stanova toga područja (koji su prostorno diferencirani unutar pograničnog pojasa Žumberka). Prikupljeni podaci statistički su obrađeni i tablično analizirani. Terenskim anketnim istraž… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In contemporary research in Croatia, it is worth emphasizing research that is directly or indirectly related to research in marginal areas: at the local level (Nejašmić, 2005;Popović and Radeljak, 2011;Nejašmić and Toskić, 2013;Feletar, 2014;Nejašmić and Toskić, 2016); research focused on land use change and the determination of landscape degradation as a feature of marginal areas (Horvat, 2013;Cvitanović and Fuerst-Bjeliš, 2018); an overview of the basic concepts of geographic marginality (Horvat and Toskić, 2017); research on social exclusion in the sense of marginalization (Šućur, 1995; Šućur, 2004; Šporer, 2004); a look at the historical aspect of marginal groups in Croatian medieval societies (Karbić, 1991); and the impact of the traffic marginality on the everyday lives of secondary school students in Zagreb (Gašparović and Jakovčić, 2014).…”
Section: Uvodmentioning
confidence: 99%
“…In contemporary research in Croatia, it is worth emphasizing research that is directly or indirectly related to research in marginal areas: at the local level (Nejašmić, 2005;Popović and Radeljak, 2011;Nejašmić and Toskić, 2013;Feletar, 2014;Nejašmić and Toskić, 2016); research focused on land use change and the determination of landscape degradation as a feature of marginal areas (Horvat, 2013;Cvitanović and Fuerst-Bjeliš, 2018); an overview of the basic concepts of geographic marginality (Horvat and Toskić, 2017); research on social exclusion in the sense of marginalization (Šućur, 1995; Šućur, 2004; Šporer, 2004); a look at the historical aspect of marginal groups in Croatian medieval societies (Karbić, 1991); and the impact of the traffic marginality on the everyday lives of secondary school students in Zagreb (Gašparović and Jakovčić, 2014).…”
Section: Uvodmentioning
confidence: 99%
“…Borderlands research in Southeast Europe (e.g., in Serbia and Croatia) has applied a range of methodological approaches to confirm the hypothesis of border regions as economically, socially and demographically marginalized parts of the national territory (Popović and Radeljak 2011;Zorko 2012;Pejnović and Kordej-De Villa 2015;Vukmirović et al 2016). In comparing the socio-economic indicators of border regions with the national average and examining the standard of living in these areas (Máliková et al 2015;Đerčan et al 2016), determining the incidence of demographic issues (Zupanc 2018;Anđelković-Stoilković 2019) and analyzing borderlands in the context of national security (Vukmirović et al 2016), multiple authors have concluded that border regions are observed through the paradigm of spatial polarization due to the disparity in the levels of development between the center and periphery.…”
Section: Introductionmentioning
confidence: 99%